Structure of the support system for military families in the United Kingdom, Germany and Slovenia - Jakopič, Matej (Sodobni vojaški izzivi, 2020)
The article aims to bring forth the anthropological and sociological characteristics affecting the military personnel and military families. It presents the structure of the support system for military families in the United Kingdom, Germany and Slovenia. For the latter, legal bases are presented regulating the support for military families, and the activities of the Comprehensive Care Section and the Military Chaplaincy, which are the only two bodies in the Slovenian Armed Forces to engage in the support of military families. The aim of the article is to contribute a piece of the answer to the big question: how to find the correct and appropriate path to help the families of Slovenian soldiers.
Keywords: celostna oskrba; comprehensive care; družina; family; military chaplaincy; military family; Slovenian Armed Forces; Slovenska vojska; vojaška družina; Vojaški vikariat